Minnesota at a Glance Quaternary Glacial Geology - Lusardi, B.A.; Dengler, E.L. (Minnesota Geological Survey, 2017)
Short summary of Quaternary glacial geology in Minnesota. Issued in 1997, updated 2017, minor update 2021. The Quaternary Period, which began about 2.5 million years ago, is divided into the Pleistocene Epoch (2.5 million to 11,700 years ago) and the Holocene Epoch (11,700 years ago to the present). Although 2.5 million years is a relatively short period of time geologically, sediments deposited during this time mask nearly all of Minnesota's previous geologic history (over 3.6 billion years!). The Pleistocene Epoch, also called the Ice Age, is marked by a series of glacial (cold) and interglacial (warm) periods. Though the Laurentide Ice Sheet (Fig. 1) covered much of northern North America throughout the Pleistocene Epoch, during interglacial periods margins of the ice sheet likely retreated significantly. Because Minnesota was at the edge of the ice sheet, it was not always completely covered with ice during glacial periods. Instead, Minnesota experienced numerous episodes of glaciation followed by ice-free periods.